Kansas Winter Annual Grass Weeds in Winter Wheat - Peterson, Dallas E.; Stahlman, Phillip W. (My University, 1995)
This publication provides farmers and ranchers with information to plan effective ways to control winter annual grass weeds in wheat.
MF2085_1995_03
Keywords: MF2085; Crops; MF